Accelerated Hydrogen Evolution Kinetics on NiFe-Layered Double Hydroxide Electrocatalysts by Tailoring Water Dissociation Active Sites - Chen, Guangbo; Wang, Tao; Zhang, Jian; Liu, Pan; Sun, Hanjun; Zhuang, Xiaodong; Chen, Mingwei; Feng, Xinliang (Advanced Materials, 2018)
Owing to its earth abundance, low kinetic overpotential, and superior stability, NiFe-layered double hydroxide (NiFe-LDH) has emerged as a promising electrocatalyst for catalyzing water splitting, especially oxygen evolution reaction (OER), in alkaline solutions. Unfortunately, as a result of extremely sluggish water dissociation kinetics (Volmer step), hydrogen evolution reaction (HER) activity of the NiFe-LDH is rather poor in alkaline environment. Here a novel strategy is demonstrated for substantially accelerating the hydrogen evolution kinetics of the NiFe-LDH by partially substituting Fe atoms with Ru. In a 1 m KOH solution, the as-synthesized Ru-doped NiFe-LDH nanosheets (NiFeRu-LDH) exhibit excellent HER performance with an overpotential of 29 mV at 10 mA cm−2, which is much lower than those of noble metal Pt/C and reported electrocatalysts. Both experimental and theoretical results reveal that the introduction of Ru atoms into NiFe-LDH can efficiently reduce energy barrier of the Volmer step, eventually accelerating its HER kinetics. Benefitting from its outstanding HER activity and remained excellent OER activity, the NiFeRu-LDH steadily drives an alkaline electrolyzer with a current density of 10 mA cm−2 at a cell voltage of 1.52 V, which is much lower than the values for Pt/C–Ir/C couple and state-of-the-art overall water-splitting electrocatalysts.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrocatalysis; hydrogen evolution reaction; NiFe-layered double hydroxide; ruthenium; water dissociation